Reasons for Not Seeking Professional Help by Abused Refugee Women: A Qualitative Study - Damra, Jalal K. (Journal of interpersonal violence, 2022)
This study aimed to gain insight into factors that have an impact on Syrian abused refugee women’s decision for seeking professional help regarding intimate partner violence (IPV) against them. This study attempted to answer the following question; what are the reasons for not seeking professional help by victims of IPV among refugee women? The qualitative method was used with semi-structured interviews in an accessible sample of 30 abused refugee women, who were identified by cooperated local community organizations working with the refugee. Five reasons emerged from the interviews affecting seeking help behaviors for refugee women: misconceptions about IPV problem; difficulties to access and approach different care centers; lack of awareness about the negative consequences of IPV; unaware, negative expectations, negative experiences, and incorrect thoughts about IPV’s services; and psychological and physical health difficulties. The authors suggested some recommendations in light of this study results. Raising awareness activities toward the negative impact of violence on women’s and children well-being, improving service availability, building professional capacities to work with abused women, and providing professional services for depressed and amputee’s refugee women.